Assessment of the Quality of Life of HIV Positive Individuals in Tertiary Care Hospitals using Whoqol-Bref Questionnaire - Umbreen Navied, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Harmonious balance in health depends upon the quality of life (QOL). QOL is the condition of life resulting from the combination of the effects of the complete range of factors such as those determining health, happiness, education, social and intellectual attainments, freedom of action, justice and freedom of expression. Aim: To assess the QOL of people affected with HIV/AIDS, which is pertinent in countries like Pakistan, as it is on the rise and one of the leading causes of stigmatization in our society as far as disease is concerned. Methods: This exploratory study by non-probability, convenient sampling was conducted on 139 selected HIV/AIDS positive and registered cases at the Voluntary Counseling Testing Centers (VCT centers) at Services and Jinnah hospitals Lahore, within 6 months in 2019. Data was collected using WHOQOL BREF Questionnaire. The SPSS software was used for data compilation and analysis. The investigator herself took the interviews, after an informed consent. Results: A total of 139cases of HIV/AIDS positive registered individuals were taken. The mean age was 32.12 ± 8.54, with 78.4% males and 21.6% females. Quality of life (QOL) tables with domains were calculated; in the WHOQOL-BREF; higher score in the domains refers to good QOL. Results of the study depicted that the highest mean score was in Social relationships domain (64.75± 16.89) and lowest mean score in quality of life & general health (41.37± 30.28). Conclusion: The study results demonstrated the dire need to explore the QOL in HIV/AIDS patients in Pakistan. There is an urge for measures to be taken, in regards to enhance the QOL. These results conclude that it is imperative to conduct health and vocational education, counseling sessions to augment awareness of the masses regarding QOL.